Profil Hepatitis B pada Pendonor Remaja - Yeni Murniasih (Poltekkes Kemenkes Semarang, 2020)
Hepatitis B is a world health problem, including in Indonesia. Hepatitis B is an inflammatory liver disease caused by the Hepatitis B virus. Blood transfusions, which are known to save lives, are one of the main routes of horizontal HBV transmission that often occurs. Reducing the potential for transmission of infectious infections through blood transfusion (IMLTD) can be done by carrying out a matched screening test or screening to detect antigens or antibodies against the disease. The screening process for Hepatitis B infection at various UTDs in Indonesia uses reactivity checks against HBsAg. The test used to detect Hepatitis B is the HBsAg examination using the Diasorin Murex ELISA (Enzyme Linked Immunosorbent Assay) method. This study provides an overview of Hepatitis B in adolescent donors. The frequency of reactive hepatitis B is quite low with the total number of donors as many as 196 people from September to November 2020. With the number of reactive as many as 3 samples (20%) with different blood groups. Seen from the age interval range 17-20 years with the number of donors voluntary sex that dominated were women. sample of teenage donors was positive 3 samples (20%) of the 196 donors who passed the screening.